Pengaruh Persepsi Bunga Bank dan Kualitas Pelayanan Terhadap MInat Menabung Pada Bank BNI Syariah di Kota Semarang - Asih Fitri Cahyani; Saryadi Saryadi; Sendhang Nurseto (Universitas Diponegoro, 2013)
Most of people in Indonesia have recognize a bank, but they know an Islamic banking in 1991 when Muamalat Bank first use syariah principle, with the “dual banking system” policy from Bank Indonesia, conventional banking can oper for syariah unit exercise. One of conventional banking that serve syariah unit exercise is BNI 46 with the name BNI Syariah. The fundamental aim of this research is to find out the effect of the interest perception and service quality to saving interest on BNI Syariah in Semarang. Type of this research is explanatory with 100 respondents taken using quota sampling, purposive sampling and incidental sampling so that the sample of this research consist of 63 respondents (customers of BNI Syariah Ahmad Yani) and 37 respondents (customers of BNI Syariah Unisula). According to the result of regression analysis, this research shows that the interest perception ang service quality are significantly influence to saving interest on BNI Syariah in Semarang 36.3 percent and 47.2 percent. So that, it is recommended to management of BNI Syariah in Semarang to maintain and to educate their customers so they know the different between conventional and Islamic banking.